Sustainable ventilation strategies in buildings: CFD research. (December 2019) - Cuce, Erdem; Sher, Farooq; Sadiq, Hamad; Cuce, Pinar Mert; Guclu, Tamer; Besir, Ahmet B.
Highlights: Sustainable ventilation strategies are analysed for school buildings. Air change rate can be enhanced 40% via stack ventilation. Stack ventilation also provides promising decrease in indoor air temperature. CO2 concentration in sustainably ventilated dorms is 800 ppm at 6:30 am. CO2 concentration in ordinary dorms is 1800 ppm, which is undesired. Abstract: Developing technology and architectural design techniques have affected the field of architecture to a great extent. As a result, human comfort has become increasingly important in recent years. A natural ventilation cooling strategy which serves as the alternative to the air-conditioning system has been effectively employed in high-rise office buildings in western countries. This paper discusses the possibility of using natural ventilation strategy in school buildings. It evaluates some of the key issues associated with natural ventilation design and school buildings, including its the types, its working principles and limitations of passive ventilation, its effects and forms of natural ventilation when used in libraries, offices, auditoriums and dormitory buildings. This work also evaluates and how does the effects of architectural design on the passive ventilation such as orientation, depth of room, the atrium and solar chimney. Based on case studies on Queens building at De Montfort University, Liberty tower of Meiji University and simulation regarding ecological dormitory building in China. These three buildings have been selected to operate as simultaneously in different climatic and thermal comfort conditions. It is concluded that single-side ventilation and cross-ventilation can have good effect on cooling and improving air quality in school buildings with different functions as long as the height and depth of rooms are properly designed. Solar wall and solar chimney can also be employed to enhance natural ventilation performance based on the principle of stack effect.